Does involving users in software development really influence system success? - Abelein, Ulrike; Sharp, Helen; Paech, Barbara (IEEE software, 2013)
Researchers have studied how best to involve users in software development for a long time, primarily in the area of information systems and human-computer interaction. The authors consider the effects of both user participation and user involvement, which they abbreviate to UPI. Existing research describes several benefits of UPI, such as improved quality due to more precise requirements, the prevention of unneeded and expensive features, and an increase in user satisfaction, which leads to higher system use. But even though some researchers consider it to be essential to system success, other studies have found contradicting results. Furthermore, it's not a common practice in today's IT projects to involve users to a large extent. To clarify UPI's effects on system success and to get a deeper understanding of the differences between user participation and user involvement, the authors reviewed the existing UPI literature in software development and conducted a systematic mapping study.